Analysis of Determinants of Economic Growth in Regencies/Cities in East Nusa Tenggara Province - Juita Hale, Yosefa Maria; Yovan, Herlulianus S. (West Science Interdisciplinary Studies, 2025)
One indicator of development progress is economic growth, which is marked by an increase in national production and income. Social issues that can affect economic growth include unemployment rates caused by an increase in the labor force that is not accompanied by an increase in job opportunities. Additionally, economic growth is also influenced by the Minimum Wage, which aims to promote economic equality, particularly for low-income workers. The goal of this study is to assess the effects of the Unemployment Rate and the Provincial Minimum Wage (PMW) on economic development in East Nusa Tenggara Province between the years 2020 and 2024. This study examines the unemployment rate, the provincial minimum wage, and economic growth in the province of East Nusa Tenggara. The approach applied in this study is quantitative description, and the analytical tool used is path analysis. Based on the analysis, it was found that the Unemployment Rate has a negative impact on economic growth with a coefficient value of -0.307 and a p-value <0.01, while the Provincial Minimum Wage has a positive impact on economic growth with a coefficient value of 0.745 and a p-value <0.01. The combined influence of both variables on economic growth is 65%.